2009
DOI: 10.1007/s10528-009-9285-8
|View full text |Cite
|
Sign up to set email alerts
|

Two Sympatric Phylogroups of the Chinese Water Deer (Hydropotes inermis) Identified by Mitochondrial DNA Control Region and Cytochrome b Gene Analyses

Abstract: Mitochondrial DNA (mtDNA) control region (927 bp) and cytochrome b gene (1,140 bp) sequences of the Chinese water deer (Hydropotes inermis) from China and Korea were obtained to examine the taxonomic status of two subspecies, H. i. inermis from China and H. i. argyropus from Korea. Two sympatric mtDNA clades (a major clade from China and Korea and a minor clade from Korea) with an average genetic distance of 2.1% in the control region and 1.3% in the cytochrome b gene were detected. These findings are not cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 11 publications
2
25
0
1
Order By: Relevance
“…Furthermore, Hu et al (2007) found that the Chinese water deer has a relatively high level of genetic diversity among microsatellite markers (n = 7) compared to other rare Cervidae, and strong differentiation between different regions of origin (mainland and Zhoushan archipelago). More recently, Koh et al (2009) reported that the Chinese and Korean subspecies seem to be very closely related, displaying low levels of genetic distance for cytochrome b (1.3%) and the control region (2.1%), which contrasts with previous expectations that the two subspecies would have distinct characteristics based on the pelage color of the deer. This previous study only focused on the taxonomic status of the two water deer subspecies (Koh et al, 2009).…”
Section: Introductionmentioning
confidence: 63%
See 4 more Smart Citations
“…Furthermore, Hu et al (2007) found that the Chinese water deer has a relatively high level of genetic diversity among microsatellite markers (n = 7) compared to other rare Cervidae, and strong differentiation between different regions of origin (mainland and Zhoushan archipelago). More recently, Koh et al (2009) reported that the Chinese and Korean subspecies seem to be very closely related, displaying low levels of genetic distance for cytochrome b (1.3%) and the control region (2.1%), which contrasts with previous expectations that the two subspecies would have distinct characteristics based on the pelage color of the deer. This previous study only focused on the taxonomic status of the two water deer subspecies (Koh et al, 2009).…”
Section: Introductionmentioning
confidence: 63%
“…More recently, Koh et al (2009) reported that the Chinese and Korean subspecies seem to be very closely related, displaying low levels of genetic distance for cytochrome b (1.3%) and the control region (2.1%), which contrasts with previous expectations that the two subspecies would have distinct characteristics based on the pelage color of the deer. This previous study only focused on the taxonomic status of the two water deer subspecies (Koh et al, 2009). Detailed genetic information about the Korean subspecies, such as the genetic diversity and population structure among various regions or localities of Korea, is scarce.…”
Section: Introductionmentioning
confidence: 63%
See 3 more Smart Citations